Wanprestasi dan Perbuatan Melawan Hukum Dalam Penyelesaian Sengketa Ekonomi Syariah - Serlika Aprita (JOURNAL of LEGAL RESEARCH, 2020)
The Islamic economic system is growing quickly in Indonesia right now. Even traditional banks have opened many branches of Islamic banks, which is one of the things that shows the growth of Islamic banks in Indonesia. Islamic law says that financial institutions should act as middlemen between people who have too much money and people who don't have enough money for business and other activities. With the creation of Government Regulations that govern Islamic Banking, the number of disputes between parties is increasing because Islamic banks are becoming more popular. In this study, a qualitative research method called "literature approach" was used. The study's results show that breaking the law means doing or not doing something that violates the rights of others, goes against the legal obligations of the person who does or doesn't do it, or goes against morals or common sense when dealing with other people or things.